2018
DOI: 10.2147/ppa.s174652
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of barriers to medication adherence among patients with uncontrolled diabetes in Qatar: integrating perspectives of patients and health care providers

Abstract: PurposeTo develop an in-depth understanding of the barriers to medication adherence among patients with uncontrolled diabetes attending primary health care (PHC) centers in Qatar by exploring and integrating patients’ and health care providers’ perspectives.Participants and methodsA descriptive qualitative methodology was used in this study. A trained researcher conducted semi-structured face-to-face interviews at two PHC centers. Patients with uncontrolled diabetes (with varied sociodemographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 45 publications
8
48
0
1
Order By: Relevance
“…Better disease knowledge and awareness about potential complications among university graduates may explain higher likelihood to attend treatment follow-up visits. [38] 190 [62] Secondary care hospital 203 123 [61] 80 [39] Primary healthcare centre 151 33 [22] 118 (78) Overall 662 274 [41] 388 [59] Entitlement to free medical care…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better disease knowledge and awareness about potential complications among university graduates may explain higher likelihood to attend treatment follow-up visits. [38] 190 [62] Secondary care hospital 203 123 [61] 80 [39] Primary healthcare centre 151 33 [22] 118 (78) Overall 662 274 [41] 388 [59] Entitlement to free medical care…”
Section: Discussionmentioning
confidence: 99%
“…The intervention to increase regularity in treatment follow-up visits may include, providing entitlement to free medical care, educational interventions for educating the patients regarding the benefits of regular treatment follow-up, motivational interviewing, family support, providing better services at healthcare settings, providing incentives to the patients on every visit for follow-up, sending reminders to the patients through phone calls, sms, and emails etc. [55][56][57][58][59][60][61][62]. There is a need to educate the patients who are at early stage of their disease to carefully follow the instructions provided by the healthcare professionals to halt further progression of their disease and its complications.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…In Kuwait, a number of studies conducted since 2006 have shown that pharmacists perceive the lack of time and staff as a barrier to counselling and providing a more educational role for patients 8,13,54,61,62. In Qatar, pharmacists have also related their lack of counselling to heavy workloads and lack of time 63. Pharmacists in New Zealand and European countries have stated that insufficient time is a barrier to pharmaceutical care implementation 64,65…”
Section: Discussionmentioning
confidence: 99%
“…For example, the healthcare providers observed that aging patients would forget to take their medications, informed patients could understand the purpose of adherence, some patients could not buy the medications, and incorrectly took their medications with insufficient time for the healthcare providers to explain the correct usage. In contrast, patients disclosed that they changed their medication dose when fasting, would not use the medications, did not believe that the medications affected maintaining blood glucose, and would be healthy without medications when returning to their home country [ 12 ]. Many of the barriers identified were directly related to patient information and knowledge about diabetes and its management.…”
Section: Introductionmentioning
confidence: 99%